Digital Learning Vocabulary Through Modern Boarding School System and Implementation in Daily Conversation - Febi, Muhammad Amin Al; Farhan, Miftah Al; Sutopo, Anam; Mukhlisin, Latutik (Universitas Muhammadiyah Surakarta, 2023)
Vocabulary is all words in the language that have different meanings and are used for the composition of a language. Vocabulary is divided into two types in daily use, namely active and passive vocabulary. Active vocabulary is words that are ready to be used and can be clearly understood by both the speaker and the listener, while passive vocabulary can only be understood by certain groups, such as conversations between a profession or a particular group of individuals. The conclusions of this research are among others, the distribution of vocabulary is carried out every morning without any holidays, the method used is direct and written so that the vocabulary that is distributed is not lost and the students can repeat it another day. Some of the obstacles experienced by the students in learning vocabulary include difficulties in memorizing, shyness and laziness in learning making the potential of the students not optimal in learning vocabulary.